Europe's Global Gateway: A new geostrategic framework for development policy? - Mark Furness; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
The proposal by the European Union (EU) to build a "Global Gateway" to the world is potentially an important juncture in EU foreign relations. Since its official launch in December 2021, most attention has been put on the initiative's geo-strategic implications and whether the EU can compete with China. Less attention has been paid to the Global Gateway's implications for EU development policy in terms of strategic objectives, decision-making, thematic focus and financing. Two aspects are important in this regard. The first is whether the Global Gateway is a serious proposal that can deliver on its headline promises to massively increase European infrastructure financing in developing countries, provide partners with an alternative economic and political model to that being offered by China, and make a meaningful contribution to their efforts to realise the 2030 Agenda. The EU's announcement that the Global Gateway will generate up to EUR 300 billion in investment by 2027 grabbed headlines, many of them sceptical. There is, however, no reason to doubt that the initiative will be adequately financed. Although the planning for the EU's international aid budget for 2021-2027 has mostly been completed, a significant proportion remains flexible and could be spent on Global Gateway projects. As for the EU's implementing capacity, the Gateway's financial toolbox draws on the EU's recent experiences with the Juncker Investment Plan and the External Investment Plan, which have both been utilised by development banks and private investors. The second aspect is whether the Global Gateway heralds a change in the EU's motivations, objectives and modalities for cooperation with developing countries and regions. On the surface, the Global Gateway does not seem to change much. There are many thematic overlaps with existing strategic frameworks for engaging with Africa and the EU's Neighbourhood. There is even a sense that the Global Gateway turns back the clock to the days when the EU focussed aid spending on infrastructure and emphasised its "political neutrality". The geopolitical context in which the EU finds itself is, however, being transformed by pandemic, wars and multipolarity. The impacts of epochal events such as the Covid-19 pandemic and Russia's invasion of Ukraine are still playing out. The Global Gateway signals a major adjustment in the EU's response to these transformations, particularly regarding its engagement with the "Global South". This will create a new paradigm for EU development policy, defined by strategic interests. It is likely that the new geostrategic framework will weaken the EU's commitment to, and observance of, core development policy principles, especially the focus on poverty, partner country ownership, open governance and the "do no harm" principle. The Global Gateway's use of aid to catalyse commercial investment risks further instrumentalising EU development policy. Specific measures are therefore needed to safeguard and promote the principles that the EU and its member states have committed themselves to.
Keywords: 330